The Influence Of Return On Investment (ROI) To Price To Book Value (PBV) - Fadilla Fadilla; Dika Perkasa; Akbar Maulana (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
This study aims to analyze the effect of profitability proxied by Return on Investment (ROI) on firm value, proxied by Price to Book Value (PBV). The study was conducted on companies from five ASEAN countries, with a sample size of 149 companies. Purposive sampling was employed as the sampling technique. Simple linear regression was used as the analysis method, using SPSS software. The results indicate that Return on Investment (ROI) has a significant effect on Price to Book Value (PBV) , evidenced by a significant value of 0.002. These findings suggest that a higher ROI corresponds to a higher Price to Book Value (PBV) for the company.